Sigurnost cestovnog prometa u Jugoslaviji i drugim evropskim državama - Radović, Blagota (Promet - Traffic&Transportation, 2012)
In its first part this paper deals with thereview of road traffic safety level fluctuationsin Yugoslavia and the R of Slovenia in the periodof the year 1970-1987.In its second part the paper provides acomparative analysis of some basic indices ofthe level of road traffic safety in Yugoslaviaand other Europeand countries in the year 1987.